Invertebrate fauna of bryophyte communities of the Petermann Island and the adjacent region of the Antarctic Penninsula - Trokhymets, V. N.; Iakovenko, N. S.; Kovalenko, O. S.; Dykyy, I. V. (Ukrainian Antarctic Journal, 2014)
A complete checklist of invertebrates inhabiting terrestrial moss communities of the Petermann Island and the adjacent region of the Antarctic Penninsula is published for the first time. We investigated the materials collected by two coauthors and performed comprehensive analysis of the published sources on the species composition of nematodes, rotifers, springtails, insects, mites and tardigrades. In the terrestrial ecosystems of the Petermann Islands found 28 species of invertebrates, with the dominating mites (11 species) and rotifers (8 species). In total, for the investigated region of Antarctic 67 invertebrate species are known, with the dominating nematodes (28 species, or 42% of the total list), mites (18 species, or 27%) and rotifers (14 species, or 21%, respectively). The most common in the moss communities of the Petermann Island are 5 nematode species, 3 species of rotifers, one species of springtails and one mite species.